2011
DOI: 10.1080/03004270903501582
|View full text |Cite
|
Sign up to set email alerts
|

How Cypriot primary school teachers promote their professional development through reflective practice

Abstract: This thesis may be made available for consultation within the University Library and may be photocopied or lent to other libraries for the purposes of consultation. Signature ………………… ABSTRACTThis study aims to examine whether and to what extent Cypriot primary school teachers understand and engage in reflective practice and the implication of this for their professional development.In particular this study explores the Cypriot primary school teachers' understanding of professional development; their engagement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…However, some studies document that school-based mentoring provides basis for staff job performance (Mudzielwan and Maphosa, 2014;Okurame, 2008). Teachers gain new knowledge when professional development is offered (Loizou, 2008). It has been discovered that one of the problems facing teachers job performance is the poor development practices offered to them by principals (Egboka, 2018;Nwite, 2016).…”
Section: Professional Support and Teacher Job Performancementioning
confidence: 99%
“…However, some studies document that school-based mentoring provides basis for staff job performance (Mudzielwan and Maphosa, 2014;Okurame, 2008). Teachers gain new knowledge when professional development is offered (Loizou, 2008). It has been discovered that one of the problems facing teachers job performance is the poor development practices offered to them by principals (Egboka, 2018;Nwite, 2016).…”
Section: Professional Support and Teacher Job Performancementioning
confidence: 99%
“…(Four teachers out of six with a teaching experience of 17-18 years: A1, A2, A4, A6; two teachers out of six with an experience of 12-13 years: B1, B3). These teachers not only espoused examining practice until substantial changes are made but they either aligned espoused beliefs and actions after reflecting on practice or underpinned their practice with more appropriate theories-in-use (see Loizou 2011). On the contrary, the teachers, whose reported changes in practice had been analysed as insubstantial, had discrepancies between espoused beliefs and actions (see Table 2).…”
Section: Resultsmentioning
confidence: 90%
“…The study showed that the primary teachers whose reported changes in practice had been analysed as substantial had espoused beliefs about change in practice and professional exchange which were aligned with their actions (Loizou 2011). (Four teachers out of six with a teaching experience of 17-18 years: A1, A2, A4, A6; two teachers out of six with an experience of 12-13 years: B1, B3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations